THE EFFECT OF FINANCIAL LEVERAGE ON PROFITABILITY SHARIA LIFE INSURANCE COMPANY - Wahyuni; Hamid, Abdul; Rismala (Institut Agama Islam Negeri Parepare, 2023)
The purpose of this study is to determine the effect of Financial Leverage on the Profitability of Jasa Mitra Abadi Tbk Sharia Life Insurance Company on the Indonesia Stock Exchange. This study uses Debt to Asset Ratio and Debt to Equity Ratio as indicators in measuring Financial Leverage and Return On Equity indicators in measuring Profitability. This research method is a quantitative associative approach by sampling financial statements in 2018-2021 using documentation techniques in the form of secondary data and data tested using partial tests (t), Chi square tests, determination coefficient tests and nonparametric Correlation tests to test hypotheses. The results obtained in this study in testing the analysis of normally distributed data requirements with a value of 0.136 can be said to be normally distributed. Based on the results of correlation and nonparametric correlation tests , it can be concluded that there is no significant relationship between the Financial Leverage variables consisting of Debt to Asset Ratio and Debt to Equity Ratio to profitability consisting of Return On Equity. Based on the results of the partial test (t), the coefficient of determination of R 2 Obtained an R square value of 0.010 or 10% with a significant value of DAR from the persial test of 0.993 > 0.05 and a DER of 0.983 > 0.05%, it can be concluded that Ho is accepted and Ha is rejected which means that there is no relationship between Financial Leverage to Profitability. Therefore, it can be concluded that variable X does not have a significant effect on variable Y. While the Chi Square result obtained a significant value of 0.238 > 0.05, it can be concluded that there is no influence between the Financial Leverage variable on profitability.